2023
DOI: 10.1002/mds.29658
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Focused Ultrasound Thalamotomy in Tremor Syndromes

James Peters,
Joel Maamary,
Kain Kyle
et al.

Abstract: BackgroundThe current literature comparing outcomes after a unilateral magnetic resonance image–guided focused ultrasound (MRgFUS) thalamotomy between tremor syndromes is limited and remains a possible preoperative factor that could help predict the long‐term outcomes.ObjectiveThe aim was to report on the outcomes between different tremor syndromes after a unilateral MRgFUS thalamotomy.MethodsA total of 66 patients underwent a unilateral MRgFUS thalamotomy for tremor between November 2018 and May 2020 at St Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Among interventional approaches, magnetic resonance-guided focused ultrasound (MRgFUS) ablation therapy is a non-invasive modality requiring neither craniotomy nor skin incision for the treatment of ET, unilateral tremor in PD or dystonia and neuropathic pain ( 4 ). It immediately appeared necessary and indispensable to structure a pathway for patients with movement disorders eligible for interventional therapies to offer them the best personalized option based on international guidelines and expert consensus and on the availability of healthcare institute in terms of expertise, facilities, technology, staff available.…”
Section: Introductionmentioning
confidence: 99%
“…Among interventional approaches, magnetic resonance-guided focused ultrasound (MRgFUS) ablation therapy is a non-invasive modality requiring neither craniotomy nor skin incision for the treatment of ET, unilateral tremor in PD or dystonia and neuropathic pain ( 4 ). It immediately appeared necessary and indispensable to structure a pathway for patients with movement disorders eligible for interventional therapies to offer them the best personalized option based on international guidelines and expert consensus and on the availability of healthcare institute in terms of expertise, facilities, technology, staff available.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the efficacy of FUS VIM ablation has been proven in multiple international studies ( 1 3 ) and recent systematic reviews, which demonstrated pooled tremor suppression of 56.7%, 62.4%, and 61.5%, respectively ( 4 7 ). Although other tremor-specific targets such as the cerebellothalamic tract ( 8 ) or even a combination of targets such as the VIM with the posterior subthalamic area (PSA) ( 9 , 10 ) have been explored, the VIM alone remains the most frequently used target in FUS treatment for ET ( 11 , 12 ). Several alternative targets have been considered in Parkinson's disease (PD) ( 13 16 ), but the VIM remains the target of choice for FUS treatment of tremor-dominant PD ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, previous studies indicate enhanced efficacy of PSA or VOA lesions in dystonic conditions, warranting a detailed subgroup analysis to understand the differential therapeutic impacts of these lesion types. [1][2][3] The study's methodology, involving the creation of additional lesions in response to residual tremor, was identified as a potential limitation in the article discussion. 1 However, a detailed quantitative analysis comparing outcomes before and after this modification in the treatment strategy is absent.…”
mentioning
confidence: 99%
“…[1][2][3] The study's methodology, involving the creation of additional lesions in response to residual tremor, was identified as a potential limitation in the article discussion. 1 However, a detailed quantitative analysis comparing outcomes before and after this modification in the treatment strategy is absent. Such an analysis is crucial to understand the full impact of this approach on tremor control.…”
mentioning
confidence: 99%